The stranger - Ray, Satyajit 1921-1992.; Dev Sen, Antara (Delhi TLM Books, 2003)
Published earlier in The Little magazine.
Screenplay.
Keywords: Uncles -- India -- Calcutta -- Drama; Inheritance and succession -- Drama